(untitled) (Eurasian Scientific Herald, 2024)
In the article, the mechanisms of development of students’ professional competence in engineering activities in higher education institutions are explained in the example of the development and application of information maps in the form of a systematic list of textual and graphic information on separate topics of the science "Engineering and computer graphics".